Effect of stem cells combined with a polymer/ceramic membrane on osteoporotic bone repair - Adriana Luisa Goncalves ALMEIDA; Gileade Pereira FREITAS; Helena Bacha LOPES; Rossano GIMENES; Selma SIESSERE; Luiz Gustavo SOUSA; Marcio Mateus BELOTI; Adalberto Luiz ROSA
Abstract Cell therapy associated with guided bone regeneration (GBR) can be used to treat bone defects under challenging conditions such as osteoporosis. This study aimed to evaluate the effect of mesenchymal stem cells (MSCs) in combination with a poly(vinylidene-trifluoroethylene)/barium titanate (PVDF-TrFE/BT) membrane on bone repair in osteoporotic rats. Osteoporosis was induced in female rats by bilateral removal of the ovaries (OVX) or sham surgery (SHAM), and the osteoporotic condition was characterized after 5 months by microtomographic and morphometric analyses. Calvarial defects were created in osteoporotic rats that immediately received the PVDF-TrFE/BT membrane. After 2 weeks, bone marrow-derived MSCs from healthy rats, characterized by the expression of surface markers using flow cytometry, or phosphate-buffered saline (PBS) (Control) were injected into the defects and bone formation was evaluated 4 weeks post-injection by microtomographic, morphometric, and histological analyses. A reduction in the amount of bone tissue in the femurs of OVX compared with SHAM rats confirmed the osteoporotic condition of the experimental model. More bone formation was observed when the defects were injected with MSCs compared to that with PBS. The modification that we are proposing in this study for the classical GBR approach where cells are locally injected after a membrane implantation may be a promising therapeutic strategy to increase bone formation under osteoporotic condition.